Choosing the right blood products for transplant patients. (29th January 2016) - Gabriel, C.
Abstract : Improving transfusion safety is a one corner stone for continuous improvements in haematopoietic stem cell and solid‐organ transplantation. In this setting, additional selection and methods are applied to blood products to ensure a sophisticated transfusion practice to support patients with high risk of bleeding as well as patients in chronic demand. Furthermore, transfusion product selection for solid‐organ and stem cell transplantation is very similar if focused on the avoidance of viral infections and adverse immune reactions.